Public Perception of Fine Dust: A Comparative Research of Participation Motives in Outdoor Physical Activities Depending on Fine Dust Concentration - Chulhwan Choi; Chul-Ho Bum (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Since the concentration of fine dust concentration in the atmosphere is rapidly increasing, recently to severe levels, and it has a fatal effect on human health, a change in people's awareness of outdoor physical activities is necessary. Nevertheless, people still take part in outdoor physical activities, even on days when a fine dust risk alert is issued, which shows that people's awareness of the danger of fine dust to their health is still lacking. This study used 341 surveys that was conducted to analyze and compare people's motives for participation in physical activities in relation to the fine dust level. After an exploratory factor analysis and reliability analysis using SPSS 23.0, the level of fine dust concentration in the atmosphere was divided into "dangerous" and "normal," while the respondents to the survey were divided into a "with fine dust group" and a "without fine dust group." People's participation motives were compared and analyzed by using a multivariate analysis of variance (MANOVA). People who participated in outdoor physical activities on days with a severe fine dust concentration showed higher scores for the motives of Competition, Appearance, Physical Condition, and Mastery, while those who participate in outdoor physical activities on days without a find dust alert showed higher scores for the motive of Psychological Condition. Countermeasures against the danger of fine dust that are more effective should be established by analyzing the motives of people who participate in outdoor physical activities despite the dangerous level of fine dust concentration in the atmosphere.